Refinement of the surgical indication and increasing expertise are associated with a better quality of pathology specimen in pleomorphic adenomas - Mantsopoulos, Konstantinos; Iro, Ann Kristin; Sievert, Matti; Müller, Sarina Katrin; Agaimy, Abbas; Koch, Michael; Iro, Heinrich (Acta Oto-Laryngologica, 2021)
Background: Traditional surgical philosophy condemns extracapsular dissection for pleomorphic adenoma as a euphemism for the enucleation of this lesion. Objectives: The aims of the study were to trace the development of surgical treatment by pleomorphic adenomas of the parotid gland over the last 15 years and explore its effects on the histopathology specimen. Materials and Methods: The medical records of all cases with pleomorphic adenomas of the parotid gland between 2006 and 2020 were examined for information on age, gender, and type of surgery. An experienced head and neck pathologist re-evaluated the histology slides from all the cases. Results: The study included 844 patients. Our analysis showed an increase in the performance of extracapsular dissection from 52.8% (2006) to 63.3% (2020), and an increase in histopathology specimens with tumours completely covered by healthy tissue from 27.7% (2006) to 50% (2020). Conclusions: Our decision-making process reached its peak in the last study years, in terms of reduced surgical invasiveness and quality of the pathology specimen. Significance: Extracapsular dissection has gained a firm hold as an indispensable tool for the experienced parotid surgeon. Proper indication is based on careful selection of cases and the correct interpretation of preoperative features on palpation and imaging.
CRIS-Team Scopus Importer:2021-01-29
Keywords: capsule; extracapsular dissection; facial nerve; Parotid gland; pathology; pleomorphic adenoma; pleomorphic adenoma